Alpha1-antitrypsin deficiency with M-like phenotype. Issue 3 (June 1977) - Kueppers, F; Utz, G; Simon, B
Abstract : A patient with a low serum concentration of alpha1-antitrypsin (0-1 g/l) but with an M-like phenotype is described. Her parents and 2 sibs have a PIM phenotype, but all except the father have approximately half-normal levels of alpha1-antitrypsin: The M-like variant apparently cannot be distinguished from M-alpha1-antitrypsin, when it occurs with M in heterozygotes. The proposita has severe airways obstruction and emphysema, and her father has moderate chronic obstructive pulmonary disease. The mother and 2 sibs are healthy.